ANALISIS INTERAKSI ADAB SEORANG MURID TERHADAP GURU DALAM PERSPEKTIF IMAM AL-GHAZALI - Anwar Yulianto; Benny Prasetiya (IMTIYAZ: Jurnal Ilmu Keislaman, 2021)
This study aims to determine the concept of a student's adab towards a teacher in the view of the book Bidayatul Hidayah by Imam Al-Ghozali. The method used in this research is library research. Primary data source is the book Bidayatul Hidayah by Imam al-Ghazali. The analysis used is a content analysis model. The results include the student precedes a teacher with respect and greeting, the etiquette of a student when speaking in front of a teacher, the etiquette of a student when asking the teacher, the etiquette of discussing with the teacher, the outward manners of students when studying with the teacher, and the inner manners of students to the teacher